Enhancing Activity in the Right Temporoparietal Junction Modifies the Effect of a High CEO-to-Employee Pay Ratio on the Perceived Investment Potential in the Construction Industry - Yang, Xiaolan; Wang, Jiaqi; Chen, Shu (Frontiers in Neuroscience, 2022)
As an increasing number of governments require the disclosure of companies’ compensation information, compensation management is becoming an important part of internal management in the construction industry. Although the literature has shown that disclosing a high CEO-to-employee pay ratio will cause various effects on the decision-making of a company’s potential investors, there is little evidence on the neural basis of such effects. Given that previous neuroscience studies have shown that the right temporoparietal junction (TPJ) is associated with altruistic behaviors, this study used transcranial direct current stimulation (tDCS) to explore the role of the right TPJ in the effects of the CEO-to-employee pay ratio on potential investors’ perceived investment potential in the construction industry. The results show that enhancing activity in the right TPJ significantly reduced the perceived investment potential of female participants, especially those with no investment experience, when the company’s CEO-to-employee pay ratio is high compared to when the pay ratio is medium. This effect was not observed in male participants. The mechanisms underlying these effects of tDCS in the right TPJ on the perceived investment potential were also explored. The main contribution of this study lies in its pioneering exploration of the neural basis of investment decision-making regarding the CEO-to-employee pay ratio. Additionally, it reveals individual feature-based differences in the role of the TPJ in investment decision-making and its possible mechanisms.